2013
DOI: 10.1002/rcm.6490
|View full text |Cite
|
Sign up to set email alerts
|

Background effects on Faraday collectors in gas‐source mass spectrometry and implications for clumped isotope measurements

Abstract: Background determination with gas flowing into the source of the mass spectrometer is necessary for accurate clumped isotope measurements of CO(2). Background corrections can be performed accurately if the slit width of the m/z 44 Faraday cup significantly exceeds that of the one for m/z 47, using a correlation between m/z 44 signal intensity and the corresponding minimum in m/z 47 background. We propose two new correction schemes that reduce the time-consuming measurement of gases of different bulk isotopic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
145
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(162 citation statements)
references
References 15 publications
2
145
0
5
Order By: Relevance
“…This had already been shown by Yeung et al (2012) to affect the measurements of O 2 and was confirmed also by Petrizzo and Young (2014). These backgrounds vary with time, instrument, and ion source conditions and show a strong negative correlation with the CO 2 pressure in the source (Bernasconi et al, 2013; Meckler et al, 2014). Because the magnitude of these backgrounds is controlled by the intensity of the m/z 44 ion beam, it affects the calculated δ 47 ratio differently for different beam intensities, requiring an intensity‐proportional correction.…”
Section: Nomenclature and Isotopic Scales For Clumped Isotopes In Carmentioning
confidence: 99%
See 1 more Smart Citation
“…This had already been shown by Yeung et al (2012) to affect the measurements of O 2 and was confirmed also by Petrizzo and Young (2014). These backgrounds vary with time, instrument, and ion source conditions and show a strong negative correlation with the CO 2 pressure in the source (Bernasconi et al, 2013; Meckler et al, 2014). Because the magnitude of these backgrounds is controlled by the intensity of the m/z 44 ion beam, it affects the calculated δ 47 ratio differently for different beam intensities, requiring an intensity‐proportional correction.…”
Section: Nomenclature and Isotopic Scales For Clumped Isotopes In Carmentioning
confidence: 99%
“…For a sample with a positive δ 47 value the relative proportion of the BG on the m/z 47 signal will be lower than that of the WG, thus leading to an overestimation of Δ 47 . This is the origin of the slope of the heated gas line, and heated gases have been used to demonstrate that negative BGs can be properly corrected after independent determination of the background in the presence of gas (Bernasconi et al, 2013; He et al, 2012). The characterization of negative background, their effect on Δ 47 and correction procedures, has been described in detail in Bernasconi et al (2013), He et al (2012), and Müller, Fernandez, et al (2017).…”
Section: Nomenclature and Isotopic Scales For Clumped Isotopes In Carmentioning
confidence: 99%
“…The Pressure Base Line (PBL) on all Faraday cups was determined on a daily basis by peak scanning at 4-5 different m/z 44 intensities as described in Bernasconi et al (52) and subsequently used for correction. The full correction scheme is described in detail by Meckler et al (53).…”
Section: Eth Measurementsmentioning
confidence: 99%
“…A tömegspektrométer detektorjain a 44-es tömegszám/töltés arányú ionsugárból származó másodla -gos elektronok negatív hátteret okoznak. A háttér korrekció (PBL -Pressure Baseline Correction, background correction) során ez a hatás kiküszöbölhető, például a 49-es tömegszám/töltés intenzitásának és a 47-es tömegszám/ töltés intenzitásának az összevetésével (BERNASCONI et al 2013. A tömegspektrométer ionforrás-állapotától függően számolni kell a δ 47 -∆ 47 értékek közötti korrelációval (scale compression, 5. egyenlet).…”
Section: A Mérés Meneteunclassified
“…Kiemelt cél a hatékonyság és a precizitás növelése, illetve a szükséges mintamennyiség csökkentése (pl. HE et al 2012, BERNASCONI et al 2013, ROSENHEIM et al 2013, CUI & WANG 2014, HU et al 2014, RÖCKMANN et al 2016. A kalibrációs munkák célja az alkalmazhatóság kiterjesztése szélesebb hőmérsékleti tartományokra (pl.…”
unclassified